Blueprint : Pocketguide CT protocol (mobile app) / Ahmad Syakir Muhamad ...[et al.] - Muhamad, Ahmad Syakir; Anuar, Muhammad Asyraf; Chawfa, Fazeamin; Salleh, Jomar (2019)
The product to be developed is a "Pocketguide CT Protocol". Pocketguide CT Protocol provides a dynamic and interactive method of viewing and studying of protocol, registration, fusion, modalities, anatomical parts and localization especially for CT-Imaging.